1997
DOI: 10.2223/jped.502
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of children with cholestatic diseases

Abstract: Objetivo: Caracterizar o grau de desnutrição e a utilidade dos índices antropométricos em crianças com doença crônica do fígado.Métodos: Foram examinados 11 pacientes, com idades variando de 5 a 105 meses. A definição do estado nutricional se fez através da determinação dos escores Z de peso para a idade (P/I) e estatura para a idade (E/I). Também se avaliou o estado nutricional através do critério de Waterlow: comparação do peso do paciente com o peso ideal para a estatura (P*), e estatura do paciente em rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
5
1
1
Order By: Relevance
“…This finding differed from the results reported by Cardoso et al, 21 who observed higher initial loss Note: For evaluation of height/age index, Z-score was categorized as very low (Z-score < −3); low (Z-score ≥ −3 and <−2); adequate (Z-score ≥ −2). For the weight/age index, as very low (Z-score < −3); low (Z-score ≥ −3 and <−2); adequate (Z-score ≥ −2 and ≤+2); high (Z-score > +2).…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…This finding differed from the results reported by Cardoso et al, 21 who observed higher initial loss Note: For evaluation of height/age index, Z-score was categorized as very low (Z-score < −3); low (Z-score ≥ −3 and <−2); adequate (Z-score ≥ −2). For the weight/age index, as very low (Z-score < −3); low (Z-score ≥ −3 and <−2); adequate (Z-score ≥ −2 and ≤+2); high (Z-score > +2).…”
Section: Discussioncontrasting
confidence: 75%
“…The estimate of fat deposits through TST and of protein content by AMC and AC are complementary data that allow for an accurate nutritional evaluation of these patients. 3,21,22 In the present study, one-third of patients showed W/A and H/A indices under −2 Z-scores. Considering the W/H index, only 12.1% of patients had Z-score lower than −2; in relation to the BMI, the percentage was 16.5%.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Previous studies revealed that the feeding practices were suboptimal, but these studies lacked detailed descriptions and analyses of dietary intake and had small sample sizes. In addition, these studies were conducted before the feeding guidelines for children with chronic cholestasis were published; thus, their conclusions were drawn through comparison to the RDA of normal children instead of cholestatic children [11,12] . Moreover, the reasons behind parents' feeding practices remain unclear, making it di cult to cost-effectively promote behavioral changes.…”
Section: Introductionmentioning
confidence: 99%